Enterprise Digital Payment Trends Survey Post COVID-19 Situation - Leon A. Abdillah; Dhea K Putri; Anggy Artavi (Universitas Negeri Semarang, 2023)
Purpose: This research article presents the results of a survey on digital payment transactions using mobile Fintech applications. The target users are from the tenant or seller side. The research locations were conducted in 2 (two) of the biggest malls in Palembang, namely Palembang Square (PS) and Palembang Trade Center (PTC).Methods: The research method applied is a survey involving online questionnaires using Google Forms.Result: The observed Fintech mobile applications are OVO and ShopeePay. The research collected data on 105 tenants of Small and Medium Enterprises (SMEs). The results show that the Fintech ShopeePay application (62%) is used more than OVO (38%). SME business actors are dominated by women (57%) compared to men (43%). These tenants are mainly in the Gen Z category (73%). Meanwhile, many of the business types of tenants are engaged in the culinary sector (42%). Most of the tenants' turnover range is in the range of 0-5 million (Rupiah) per month (38%). but there are 2% who have a turnover of more than 25 million (Rupiah).Novelty: This research enriches the survey on the use of the Fintech platform from the side of tenants who open their businesses in modern shopping places after COVID-19.